2021
DOI: 10.3389/frsc.2021.692018
|View full text |Cite
|
Sign up to set email alerts
|

Species and Metabolic Pathways Involved in Bioremediation of Vietnamese Soil From Bien Hoa Airbase Contaminated With Herbicides

Abstract: Four bacterial strains were isolated from enrichment cultures inoculated with soil from Bien Hoa military base in Vietnam contaminated with the herbicides 2,4-dichlorophenoxyacetate (2,4-D) and 2,4,5-trichlorophenoxyacetate (2,4,5-T). They were classified as Pseudomonas aeruginosa BT1 2.2, Sphingomonas histidinilytica BT1 5.2, Bordetella petrii BT1 9.2, and Achromobacter xylosoxidans BT1 10.2. All four were able to degrade 2,4-D and 2,4,5-T, but only the last three species used them as the sole sources of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…A blastn-search revealed seventeen (excluding canonical tfd I ) gene clusters which had an over 90% match with the tfdB I F I E I D I C I T structure of the tfd I gene cluster. They were designated as tfdT1T2CD (unpublished), tfdCDEF or tfdT-CDEF [ 35 , 45 ], tfdCDEF [ 58 ], tfdFEDCT [ 43 ], tfdB I F I E I D I C I T [ 44 ], tfdBFEDC , tfdBFET [ 5 ], tfdBFEDCS [ 7 ] or not annotated (CP016005, CP026110) ( Table S1 ). Fourteen of those seventeen tfd I gene clusters were located on plasmids in species belonging to the Burkholderiaceae family.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A blastn-search revealed seventeen (excluding canonical tfd I ) gene clusters which had an over 90% match with the tfdB I F I E I D I C I T structure of the tfd I gene cluster. They were designated as tfdT1T2CD (unpublished), tfdCDEF or tfdT-CDEF [ 35 , 45 ], tfdCDEF [ 58 ], tfdFEDCT [ 43 ], tfdB I F I E I D I C I T [ 44 ], tfdBFEDC , tfdBFET [ 5 ], tfdBFEDCS [ 7 ] or not annotated (CP016005, CP026110) ( Table S1 ). Fourteen of those seventeen tfd I gene clusters were located on plasmids in species belonging to the Burkholderiaceae family.…”
Section: Resultsmentioning
confidence: 99%
“…This group combines non-traditional clusters that have variable gene structures and significantly differ from the canonical tfd gene clusters of the I and II types. The published clusters were annotated as dccEA I D I , dccA II D II , dccEA I D I [ 62 ], tfdC2E2 , tfdC2E2F2 , tfdDRFCE , tfdDRF [ 38 , 63 ], cnbCDEF [ 64 ], tfdBCDEFKR [ 41 ], tfdEC , tfdCE [ 7 ], tfdBaFRDEC [ 10 ], tfdEICIFIRDI , K , BI and tfdDII , FIIEIICII , BII [ 46 ]. Nevertheless, comparative genomic analysis showed that the genetic structure of this tfd IV type cluster could be divided into three main subtypes—A, B and C ( Figure 2 a) (details of the new classification and nomenclature are described in the Section 3 and Section 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is no direct evidence for the involvement of Bordetella and Sphingomonas in the degradation of 2,3,7,8-TCDD, the fact that they are relatively dominant in these 2 types of culture makes it a likely assumption. It has been shown earlier that species from the genera Bordetella and Sphingomonas have the genes encoding the enzymes degrading 2,4-D and 2,4,5-T, and indeed use that potential to degrade these herbicides ( Nguyen et al, 2021a , b ). We suggest that the presence of the herbicides 2,4-D and 2,4,5-T in the soil has contributed to the bioremediation results.…”
Section: Discussionmentioning
confidence: 99%